Interest of neuroimaging of social exclusion in suicide. Issue 4 (1st September 2018) - Olié, Emilie; Courtet, Philippe
Abstract: With one million deaths worldwide, suicide is a major health issue. The frequency of life events preceding suicidal act is high and raises the question of their role in suicidal process. At biological level, dysfunctional neural processing of social exclusion may participate in suicidal risk through an increased perception of social adversity in vulnerable subjects. The purpose of this narrative review is to discuss neuroimaging findings related to social exclusion and loneliness, and to open new perspectives to investigate sensitivity to social stress in suicide.